IPSASs adoption and implications on the differences in GA-NA budgetary balances: - Jesus, M.; Jorge, S. F.; Laureano, Raul M. S. (Spring workshop of the EGPA XII Permanent Study Group Public Sector Financial Management, 2015)
IPSASs are praised as a good reference to provide for a harmonized micro-accounting system allowing for more transparency and quality in public sector accounting across EU member-States, so that governmental accounts are more reliable and trustable, both for management purposes and to investors in capital markets. Macroeconomic aggregates reported by these countries may be better comparable and accurate. However, questions remain concerning IPSASs contribution to the convergence between Governmental Accounting (GA) and the National Accounts (NA). This is remarkably important given that macroeconomic information (NA) is derived from microeconomic accounting (GA), particularly from the micro-budgetary reporting systems, mainly cash-based, hence requiring for adjustments when translating data from micro into macro accounting. This paper assess how the proximity to an IPSAS-based accounting and reporting system in GA has impact on the diversity and materiality of GA-NA budgetary balances (deficit/surplus) adjustments, hence analyzing whether IPSASs might contribute to the reconciliation GA-NA, reducing the number and amount of adjustments to be done when moving from the micro into the macro reporting system. The analysis is especially relevant in the current EU context where EPSASs are being considered as derived from, or inspired by, IPSASs. Main findings show that IPSASs per se do not make considerable difference in terms of GA-NA adjustments diversity and materiality, so IPSASs-based EPSASs will hardly contribute to approaching GA into NA and improving Government Finance Statistics (GFS) reliability. EU policy-makers must be aware that EPSASs might become relevant in reconciling GA and NA only and when they address budgetary accounting and reporting or when countries move to accrual-based budgets.